Contemporary Trends and Outcomes in Patients With ST-Segment Elevation Myocardial Infarction and End-Stage Renal Disease on Dialysis: Insight from the National Inpatient Sample - Khan, Muhammad Zia (Cardiovasc Revasc Med, 2020)
BACKGROUND: Cardiovascular disease is the major cause of mortality in end stage renal disease (ESRD) patients on dialysis and myocardial infarction constitutes almost 20% of such deaths. We assessed the trends, characteristics and in-hospital outcomes in patients with ESRD. METHODS: We used national inpatient sample (NIS) to identify patients with ESRD presenting with ST-segment elevation myocardial infarction (STEMI) for calendar years 2012–2016. Multiple logistic regression analysis and propensity matched data was used to compare outcomes for the purpose of our study. RESULTS: Patients on dialysis who presented with STEMI were less likely to be treated with emergent reperfusion therapies including percutaneous coronary intervention, bypass graft surgery and thrombolytics with in first 24 h. In propensity-matched cohort, the mortality was nearly double in patients who have ESRD compared to patients without ESRD (29.7% vs. 15.9%, p < 0.01). In-patient morbidity such as utilization of tracheostomy, mechanical ventilation and feeding tubes was also more prevalent in propensity matched ESRD cohort. In multivariate regression analysis, ESRD remains a strong predictor of increased mortality in STEMI patients (OR 2.65, 95% CI, 2.57–2.75, p < 0.01). CONCLUSION: Our study showed low utilization of evidence-based prompt reperfusion therapies in ESRD patients with STEMI along with concomitant increased poor outcomes and resource utilization. Future research specifically targeting this extremely high-risk patient population is needed to identify the role of prompt reperfusion therapies in improving outcomes in these patients.